Hermeneutics Study in Pappaseng Tau Ugi of the Bugis Bone Community on the Interpretation of Warani Values and Getteng Values - Ana Suka Dema; Hajrah Hajrah; Suarni Syam Saguni (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. This study aims to describe the interpretation of the value of warani and the value of getting on pappaseng ugi of the Bugis Bone community using Hermeneutics studies. This research is a descriptive qualitative research type. The data source of this research is pappaseng ugi of the Bugis Bone community from the results of the interview. The data of this study is the pappaseng citation which is included in the warani value or the value of getting pappaseng tau ugi of the Bugis Bone community. The data were collected using interview techniques by following the reduction steps, including presenting the data, concluding and verifying the data. The results showed that pappaseng tau ugi is still used and believed by the people of Bone to this day, and pappaseng consists of various kinds, one of which is pappaseng which contains warani values and getteng values.Keywords: Culture, pappaseng, warani, getteng